Assessing Environmental Literacy Knowledge of Early Childhood Education Teachers in District Mardan - Nazeer Rahman; Dr. Jahan Ara Shams; Dr. Muhammad Zafar Iqbal (Social Science Review Archives, 2025)
One of the biggest problems in regard to sustainable development is environmental degradation, which is especially typical of developing countries such as Pakistan. Early Childhood Education (ECE) teachers are involved in influencing environmental awareness of children, yet there is little to be found about their own environmental literacy. The paper evaluated the level of environmental literacy of ECE teachers in District Mardan. A structured questionnaire was used to survey 100 teachers with semi-structured interviews with 12 teachers being used to complement the survey. Findings indicated that although teachers were generally aware of such issues as pollution and deforestation, their conceptual understanding of the topics of biodiversity, climate change and sustainable practices was low. Interviews revealed gaps in the curriculum, lack of training and use of personal experiences as opposed to structured knowledge. The research ends that environmental literacy should be reinforced in ECE level in Pakistan by undertaking professional development and curriculum reform.